Analisa Kualitas Air di Sungai Pelus, Purbalingga, Jawa Tengah - Rizki Andrianto; Ima Yudha Perwira; I Ketut Wija Negara (Current Trends in Aquatic Science, 2021)
The purpose of this study was to determine the level of water quality in the Pelus River, Purbalingga Regency, Central Java. Water sampling is carried out in the upstream, middle and downstream sections, from June 2019 to July 2019. The water sample was then analyzed for the content of water quality parameters including COD and BOT measured using permanganate-based Titrimetry method, DO is measured using the Winkler method, TSS is measured using the Gravimetric method, then the TDS is measured using a TDS meter, Turbidity is measured using a Turbidity meter, then Nitrate and Phosphate are measured using the Spectrophotometry meth od, and water pH is measured using a pH meter. The results showed an increase in the value of water quality temporally and spatially ie (COD 28-43 mg/L, BOT 8.4-11.3 mg/L, DO 7.3-5.7 mg/L, TSS 32-65 mg/L, TDS 98-168 mg/L, Turbidity 7.2-12.7 NTU, Nitrate 0.8-1.4 mg/L, Phosphate 0.3-0.5 mg/L and pH 6.8-6.6). Temporal and spatial increase in the value of water quality, allegedly due to rainfall and high atropogenic activity in the Pelus River. Keywords: Pelus River; water quality; pollution; Purbalingga